The Relationship of Self Efficacy towards Improving Quality of Santri Organization in Daar El-Qolam - TAUFIK ABDILLAH SYUKUR; AISHA TARA ATHIRA (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2019)
In this modern era, for its rapid grown, Pesantren has played an important role in the development of Indonesian education. Daar El-Qolam is an institution based on a modern pesantren system that has a principle to create a good future generation. By using their principle and implement it to all santri, it is expected that it can increase their lead. In actualizing their purpose, pesantren has created a good system both academic and non-academic. To improve their abilities, santri needs a place and chance to increase and to improve their abilities. One of the pesantren programs is to obligate all santri from class 5 to be a manager in daily activities in pesantren. The purpose of this study case is to know the relationship of self-efficacy in improving the quality of santri organization in Daar El-Qolam. The method used in research was quantitative research design that used correlational method method to know the relationship of Self-Efficacy in improving Quality of Santri Organization in Daar El-Qolam. Based on the result of research that has been done regarding the relationship of Self efficacy towards improving santri organization in Daar El-Qolam, there was the significant relationship of Self efficacy in improving quality of santri organization in Daar El-Qolam.